Trilogy in Minor Solos - Thürler, Djalma (2023)
This article intends to reﬂect on the relationships between art, society, and politics in the laboratory practices of ATeliê voadOR. Thus, it is intended to analyze the discursive and performative strategies, focusing on three of its solo shows: Three Cigarettes & The Last Lasagna, The Other Side of All Things, and An Impossible Woman, and how these perform the critical function of encompassing and reshaping the dynamics of conﬁguring a more just and democratic society in Brazil from the first decade of the 21st century.